Analyzing Berger Paints from Financial Perspective - Abdul Rahman; Dr. Prasanna Kumar (International Journal of Engineering and Management Research, 2022)
The main objective of this paper is to analyze the overall financial position and liquidity of the company using ratio analysis. It shows the firm’s development (if any) of the previous 5 years. The secondary data is used for the entire study i.e. the last five years annual reports of Berger paints. Ratio analysis helps us to draw a comparison within the firm and outside the firm. The tabular representations of data are used for better understanding of the position of the firm and to compare one year with another within one go. Ratios are useful tools for the key members of the firm and they include the management, financiers, shareholders and creditors etc. Various types of ratios like liquidity ratios, profitability ratios, and solvency ratios are analyzed in this study. This paper tells not only about the financial position of the firm but also helps to identify the problems and offer suggestions to improve its performance.